HUBUNGAN MOTIVASI BELAJAR DAN KARAKTERISTIK KEPRIBADIAN GURU DENGAN HASIL BELAJAR MEMBACA - DASUKI, DASUKI (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
The objective of the research is to find out the relationshep (1) the correlation between learning motivation and personality of early reading, (2) the correlation between learning motivation and personality of early reading,, and (3) the correlation between learning motivation and personality of early reading, The research was conducted at Munjul Primary School of East Jakarta, with 32 of 2nd those grade students of academic year 2008/2009. The sample was taken by proportional sampling techniques. The data of personality techer of early reading were collected through test, whereas, the learning environment and motivation data were collected through questionnaire. The data were analyzed by regression of the research and correlation analysis.The result of the research showed that: (1) there is a positive relation between learning motivation and learning personality of early reading, (2) there is a positive relation between learning personality techer of early reading, and (3) there is a positive relation between personality techer with learning of early reading. Finally it can be concluded that learning motivation and personality of early reading.Keywords: motivation, personality of teacher, early reading